2023
DOI: 10.3390/medicina59020354
|View full text |Cite
|
Sign up to set email alerts
|

Urinary microRNA in Diabetic Kidney Disease: A Literature Review

Abstract: Diabetic kidney disease is the most common primary disease of end-stage kidney disease globally; however, a sensitive and accurate biomarker to predict this disease remains awaited. microRNAs are endogenous single-stranded noncoding RNAs that have intervened in different post-transcriptional regulations of various cellular biological functions. Previous literatures have reported its potential role in the pathophysiology of diabetic kidney disease, including regulation of Transforming Growth Factor-β1-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Urinary exosomes offer a comprehensive perspective on the entire urinary system [17]. Previous studies have indicated its potential involvement in the pathogenesis of diabetic nephropathy, including the control of fibrosis through transforming growth factor β1, the extracellular matrix and cell adhesion proteins, cellular hypertrophy, growth factor regulation, cytokine production, and activation of the redox system [18].…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Urinary exosomes offer a comprehensive perspective on the entire urinary system [17]. Previous studies have indicated its potential involvement in the pathogenesis of diabetic nephropathy, including the control of fibrosis through transforming growth factor β1, the extracellular matrix and cell adhesion proteins, cellular hypertrophy, growth factor regulation, cytokine production, and activation of the redox system [18].…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…MicroRNA is found to play important roles in the pathophysiology of diabetic kidney disease. Lee et al [13] examine the potential applications of urinary microRNA on diabetic kidney disease from the emerging experimental and clinical evidence. While the results of using urinary microRNA as a non-invasive disease marker to predict diabetic kidney disease appear promising, further experimental standardization and clinical verification trials are warranted to promote its application practically.…”
mentioning
confidence: 99%
“…(Padilla-Martínez et al, 2021) microRNA Prognostic hsa-miR-126, hsa-miR-29a, hsa-miR-133b, hsa-miR-342, hsa-miR-30a, and others(Lee et al, 2023) …”
mentioning
confidence: 99%